PENGARUH VARIASI WARNA PLAT KOLEKTOR SURYA TERHADAP KINERJA PEMANAS AIR TENAGA SURYA - SE, Harizalni; Muttaqin, Aris Zainul; Mulyadi, Santoso (ROTOR, 2014)
Solar water heaterÂ is a deviceÂ that heats water usingÂ solar collectors as a heat absorber ofÂ solarÂ radiationÂ that isÂ transmittedÂ toÂ the pipe containing waterÂ . InÂ this research, comparative performanceÂ testing of solar water heating to solar collector plate color variations . Variations of color used is black ( black ) no. ( 39 ) with the brand of quick drying formula zuper spray acrylic spray paint , red ( red signal ) no. ( 23 ) with rj LONDON acrylic paint brand epoxy spray paintÂ , and blueÂ ( blueÂ fluorescentÂ ) no.Â ( 1004) with rj LONDON acrylic paint brand spray paint epoxy Data collection was performed byÂ taking data every 30 minutesÂ for 3 hours are 9:00 to 12:00 pm at the clock and the test performed 3 times on different days . Data taken from the study include inlet and outlet water temperature collectors , and the temperature of the water in the tank , which is then carried out data processingÂ to determineÂ theÂ flow rateÂ ,Â the density of waterÂ ,Â the waterÂ temperature difference in and out collectorÂ ( ÃTÂ )Â ,Â the performance of solar water heatersÂ ( qÂ )Â , and processingÂ the data graphically . The results of the study of each color plate solar collector plate showed that the color black has the highest absorption compared with red and blue , because the color black has emissivity close to 1 ( objects that are almost black)Â is aÂ transmitter as well as a good heat absorber. Kata kunci: Kolektor, emisivitas, warna plat, air